The institutional framework for a sufficiency driven economy - Schneidewind, Uwe; Zahrnt, Angelika (Ökologisches Wirtschaften - Fachzeitschrift, 2014)
Sufficient lifestyles can be considered both necessary and desirable on a personal level, but supporting framework conditions need to be created politically. This includes overall economic policy and its goals as well as specific sectors like mobility, education or health policy.